2003
DOI: 10.1046/j.1365-3180.2003.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between speed, soil movement into the cereal row and intra‐row weed control efficacy by weed harrowing

Abstract: Summary Field trials were carried out at a single Danish and two Spanish locations. In Denmark, winter wheat was sown at 24‐cm row spacing allowing hoeing in the inter‐row area. Hoeing speeds of 2, 5 and 8 km h−1 were tested at the end of tillering, at the beginning of stem elongation or on both occasions. The crop was harrowed immediately after hoeing at the same speed. At the Spanish locations the winter barley was sown at a 12‐cm row spacing and harrowed only, at either pre‐emergence plus post‐emergence, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 9 publications
3
38
1
Order By: Relevance
“…Rasmussen (1990), however, did not find a clear relationship between both. Also Cirujeda et al (2003) did not find efficacy increases when comparing 2, 5 and 8 km h -1 and Rydberg (1993) described the biggest weed reduction at 5 km h -1 and increasing harrowing speed up to 9 or 13 km h -1 did not improve weed control but could affect grain yield.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Rasmussen (1990), however, did not find a clear relationship between both. Also Cirujeda et al (2003) did not find efficacy increases when comparing 2, 5 and 8 km h -1 and Rydberg (1993) described the biggest weed reduction at 5 km h -1 and increasing harrowing speed up to 9 or 13 km h -1 did not improve weed control but could affect grain yield.…”
Section: Introductionmentioning
confidence: 91%
“…It tills the soil surface superficially, so that weed seedlings are uprooted and covered by soil. Some authors have suggested that the most important effect is covering (Jones et al, 1995), while in other experiments uprooting was probably the main cause (Kurstjens and Kropff, 2001;Cirujeda et al, 2003). Uprooting and covering may not completely kill the weeds, but the damage caused may be enough to slow down their growth (Lambain et al, 1993) although Rasmussen (1992) did not find that surviving weeds had a lower competitive ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under favourable conditions, weed harrowing may provide similar efficacy as herbicides but usually the control effects from harrowing are lower than those which can be achieved with chemical control. Efficacy of harrowing depends on many factors including crop species and weeds present, the development stages of crop and weeds, weather, soil type and harrow type (Cirujeda et al, 2003;Hansen et al, 2007;Jensen et al, 2004;Rydberg, 1994). Weed harrowing may be divided into two categories; pre-emergence harrowing, and post-emergence harrowing.…”
Section: Weed Harrowingmentioning
confidence: 99%
“…In particular, the recent automated harrowing systems designed to vary in real-time the harrowing intensity, on the basis of crop and weeds detection by sensors, have showed to increase the harrowing efficacy and balance the trade-off between crop damage and weed control (Rueda-Ayala et al, 2013). Indeed, harrowing intensity refers to the cultivation aggressiveness of the tines penetrating into the soil surface that can be varied by varying the tine angle relative to a perpendicular axis to the field surface, varying the depth of the implement, varying driving speed or through various consecutive passes on the same day of cultivation (Cirujeda et al, 2003;Rasmussen et al, 2007). All these setting parameters can be manually or automatically adjusted; however, changing the harrowing intensity by varying the tine angle seems the most appropriate way to develop an automated harrowing system (Rueda-Ayala et al, 2015).…”
Section: Introductionmentioning
confidence: 99%